2013
DOI: 10.1016/j.exer.2012.12.008
|View full text |Cite
|
Sign up to set email alerts
|

A reduced zinc diet or zinc transporter 3 knockout attenuate light induced zinc accumulation and retinal degeneration

Abstract: Our previous study on retinal light exposure suggests the involvement of zinc (Zn2+) toxicity in the death of RPE and photoreceptors (LD) which could be attenuated by pyruvate and nicotinamide, perhaps through restoration of NAD+ levels. In the present study, we examined Zn2+ toxicity, and the effects of NAD+ restoration in primary retinal cultures. We then reduced Zn2+ levels in rodents by reducing Zn2+ levels in the diet, or by genetics and measured LD. Sprague Dawley albino rats were fed 2, or 61 mg Zn2+/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Previous studies have reported that Zn plays an important role in photoreceptor ischemia-mediated cell death, which can be diminished by pyruvate and nicotinamide, probably by restoring NAD + levels. 71 Bai et al 72 demonstrated that a reduced Zn 2+ diet decreased the Zn 2+ staining and degeneration of photoreceptors under intense visible light, and Zn 2+ staining and photoreceptor cell death were observed less in ZnT3-KO (no synaptic Zn 2+ ) mice. In this study, we also found that the OS was more sensitive to the toxicity of high Zn levels than the IS, which was associated with a higher content of Zn in the photoreceptor OS.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous studies have reported that Zn plays an important role in photoreceptor ischemia-mediated cell death, which can be diminished by pyruvate and nicotinamide, probably by restoring NAD + levels. 71 Bai et al 72 demonstrated that a reduced Zn 2+ diet decreased the Zn 2+ staining and degeneration of photoreceptors under intense visible light, and Zn 2+ staining and photoreceptor cell death were observed less in ZnT3-KO (no synaptic Zn 2+ ) mice. In this study, we also found that the OS was more sensitive to the toxicity of high Zn levels than the IS, which was associated with a higher content of Zn in the photoreceptor OS.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These transport proteins function as multimers (21). ZnT3 knockout mice do not load Zn 2+ in synaptic vesicles and therefore are resistant to neuronal injury after light damage, global ischemia, or hypoglycemia (22,23 and C.T.S. and L. Wei, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the rest of extra photons are absorbed by the retinal pigment epithelium or choroid to avoid heat accumulation[ 11 , 12 ]. However, due to the direct effect of light energy, photoreceptor cells and RPE are also the most vulnerable tissues when the light irradiates abnormally[ 13 ]. Moreover, animal study found müller glia cell activation paticipated in a laser-induced retinal degeneration and regeneration in zebrafish[ 14 ].…”
Section: Discussionmentioning
confidence: 99%